Dancing-Girls and Bayadères: Challenging Representations of Indian Temple Women - Case, Vannessa. (Tufts University. Tisch Library., 2023)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of Music.; Advisor: Melinda Latour.; Committee: Stephanie Khoury, and Kareem Roustom.; Keyword: Music history.